2023
DOI: 10.3390/f14081678
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Microbial Residue and Its Contribution to SOC between Organic and Mineral Soil Layers along an Altitude Gradient in the Wuyi Mountains

Yiming Sun,
Xunlong Chen,
Anna Zhong
et al.

Abstract: Microbes are crucial components of soil, and their residue carbon plays a significant role in the formation and stabilization of soil carbon pools. However, current research on microbial residue carbon has predominantly focused on surface soils, with limited studies on deep soils. The patterns of variation along soil profiles and their controlling factors remain unclear. Therefore, this study aimed to investigate the soils from different elevations in the Wuyi Mountains, specifically focusing on the organic la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Natural physiological stressors also significantly influence the adaptive mechanisms of trees, including leaf damage [9], life stages [10], seasonal cycles [11], and altitude gradients [12].…”
Section: Adaptation To Natural Physiological Stressorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural physiological stressors also significantly influence the adaptive mechanisms of trees, including leaf damage [9], life stages [10], seasonal cycles [11], and altitude gradients [12].…”
Section: Adaptation To Natural Physiological Stressorsmentioning
confidence: 99%
“…Microbial residue carbon plays a significant role in soil carbon formation, affecting tree growth. Sun et al [12] investigated amino sugars as biomarkers for microbial residue carbon in organic and mineral layers across different elevation gradients in the Wuyi Mountains. The results showed that more residue carbon content derived from fungi than bacteria in soil, with the ratio of fungal residue carbon to bacterial residue carbon decreasing from the organic layer to the mineral layer.…”
Section: Adaptation To Natural Physiological Stressorsmentioning
confidence: 99%